Development of a theoretical multifaceted process model of shame : a qualitative study of Malays - Aknouche, Nadjet (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The present research aimed to weave a theoretical process model of shame. Mainstream psychology views shame as a unitary construct that is conclusively pathogenic. In the present research a tentative theoretical framework that encompasses adaptive and maladaptive forms of shame based on the interface between shame and different forms of self-esteem was developed. A qualitative study was conducted to enrich the preliminary theoretical framework into an overarching process model by investigating shame-inducing situations in the Malay context and the role of different self-conceptions in steering multiple forms of shame and their corresponding behavioural outcomes. Data was collected from a total of 146 Malay participants attending four Malaysian universities. Participants were asked to describe two events in which they felt ashamed and describe in detail their behavioural and affective reactions to shame experience. A systematic method of thematic analysis was utilised to code the raw data. The results indicated that though shame was engendered by a broad range of situations, the most common situational determinant of shame was negative evaluation. An unexpected inducer of shame appeared in the analysis reflected a generalised state of shame. Coding analysis yielded to a number of selfconceptions. An adaptive form of shame was evoked as a result of private feelings of self-discrepancy. Maladaptive forms of shame were elicited as a result of feeling persistently deficient, a concern with others evaluation of the self, and an adopted self (rigid and immune). Behavioural outcomes varied by virtue of different selfconceptions from anticipatory to reactive on the one hand and from genuinely (e.g., self-improvement) to maliciously motivated (e.g., self-protection, and selfenhancement) on the other. Discussion focused on interpreting the findings in light of self-discrepancy theories and how these results enriched the initial theoretical framework. Predicated on the qualitative study, a process model of a multifaceted conception of shame was proposed with nine pathways assumed to lead to different forms of shame with distinct forms of behavioural outcomes. The constructs posited to determine shame and its behavioural responses were self-knowledge and selfawareness. Three processes interconnect these two units to shame, namely, a precipitating negative event, the activation of self-knowledge, and self-comparison. The described theoretical framework departed from other previous adduced models in (1) the multiplicity of shame and its behavioural responses; (2) the proposed adaptiveness of shame; (3) the role of self-knowledge (affective and cognitive) in defining shame and its consequences; and (4) the bidirectional relationship between shame and the self. General discussion focused on the affinity of these findings with and their departure from previous research. Implications of both the qualitative study and the developed process model for future research, therapeutic interventions, and their respective limitations were discussed.